Ventilatory efficiency and the selection of patients for heart transplantation - Ferreira, António M.; Tabet, Jean-Yves; Frankenstein, Lutz; Metra, Marco; Mendes, Miguel; Zugck, Christian; Beauvais, Florence; Cohen-Solal, Alain (Circulation. Heart failure, 2010)
Background— - - Ventilatory efficiency, assessed by the slope of minute ventilation (Ve) versus carbon dioxide production (Vco2), is a powerful prognostic marker in patients with chronic heart failure. We hypothesized that Ve/Vco2 slope would be more accurate than the current listing criteria for heart transplantation (HTx) in identifying patients likely to derive a survival benefit from this intervention. - - Methods and Results— - - A total of 663 patients with chronic heart failure who underwent cardiopulmonary exercise testing were tracked for cardiac mortality and HTx. Ve/Vco2 slope was the strongest independent predictor of mortality. Using a Ve/Vco2 slope threshold instead of the current exercise criteria would classify 39 more subjects as being high risk (196 versus 157), correctly identifying 19 more patients who died during follow-up (57 versus 38) and 16 others who underwent transplantation (52 versus 36). Unlike the current listing criteria for HTx, Ve/Vco2 slope provided significant discrimination between the 3-year survival of high- and low-risk patients and posttransplant patients selected from the International Society for Heart and Lung Transplantation registry. Reanalysis of survival data using death or HTx as the end point showed similar results. - - Conclusions— - - Ve/Vco2 slope is more accurate than the current listing criteria for HTx in identifying patients likely to derive a survival benefit from HTx.
Gesehen am 13.06.2023